The Influence Of Compensation And Motivation On The Performance Of Customer Service Employees At Telco Company In Indonesia - Yogie Pranata, Mochamad; Wulansari, Puspita (Publisher Cv. Inara, 2025)
This study examines the influence of compensation and work motivation on the performance of customer service employees at GraPARI Telkomsel in West Java. Using a quantitative approach, data were collected from 105 employees via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that both compensation (t-statistic = 7.655, p = 0.000) and motivation (t-statistic = 5.631, p = 0.000) significantly and positively affect employee performance. Collectively, these variables explain 86.2% of performance variance (R² = 0.862). The findings underscore the critical role of equitable compensation systems and motivational strategies in enhancing service quality in the telecommunications sector. Recommendations include revising compensation packages and fostering intrinsic motivation through recognition and career development.